EFL learners' preference for corrective feedback strategies in relation to their self-perceived levels of proficiency - Kanokpan Wiboolyasarin; Watcharapol Wiboolyasarin; Nattawut Jinowat; Ruedee Kamonsawad (English Language Teaching Educational Journal, 2022)
The purpose of this work was to address the overarching questions of how EFL Thai learners preferred corrective feedback strategies and whether there were any significant differences in preferences across learners’ language ability levels. The quantitative study collected 418 Thai EFL learners’ preferences for corrective feedback via a closed-ended Likert scale questionnaire. The survey showed that learners desired to edit when their speech or writing contained errors, particularly when the wrong utterance was responded to with a metalinguistic comment regarding the error’s nature. Statistical analysis found significant differences in students’ preferences for metalinguistic clues and public feedback between intermediate and elementary levels. It appeared that beginner-level learners would almost certainly experience embarrassment if they were corrected in front of their peers. Conversely, self-correction, which was necessary once the student’s erroneous remark was explained in terms of grammar usage, probably made advanced students uncomfortable. While teachers should examine their EFL students' corrective feedback preferences, this study found that their proficiency levels were slightly relevant.